Assessment of Murky Water and its Conductivity During Dry and Rainy Seasons in Combeima River (Ibagué, Colombia) - Ospina Zuñiga, Oscar; García Cobas, Georgina; Gordillo Rivera, Jorge; Tovar Hernández, Katerine (Ingeniería Solidaria, 2016)
Introduction: these are findings of the research project “Evaluation of pollutant load in Combeima River, main supply source of Ibague’s urban aqueduct” developed by the Cooperative University of Colombia in Ibagué.Methodology: an exploratory research was conducted to evaluate the spatial behavior of murky river water and its conductivity in 2014; the quality samples were collected from unprocessed water in seven different points along the river. The research was performed during dry and rainy seasons, and analyzed during the covered period between 2008 and 2012. The dry and rainy seasons during that time were characterized by natural meteorological events known as El Niño and La Niña.Results: the highest monthly average values were recorded in May, period that matches the first rainy season and that evidences an average yearly increase. The conductivity had no variations during the course of a year. The findings include concentrations allowable for human consumption, in which the weather conditions did not had a significant impact, despite changing values of the murky water, to which it is not linked.Conclusion: the company IBAL S.A. E.S.P. proposed a medium-term solution to alleviate the effects of increased murky water during rainy seasons, via the study, design and construction of satellite water intakes at the sources that, given their volume and running conditions, may be beneficial as substitute systems during periods where it’s imperative to close the aqueduct’s water intake.